Diagnosis and treatment of liver metastases of parathyroid carcinoma - Su, Chaoyun; Zhang, Junwei; Yang, Huayu; Xu, Yiyao; Lu, Xin (Frontiers in Endocrinology, 2022)
Abstract Introduction: Parathyroid carcinoma (PC) is a very rare endocrine malignancy occurring in less than 1% of all cases of primary hyperparathyroidism（pHPT). Liver is the second most common target organ for distant metastases of PC, but there are no guidelines for the diagnosis and treatment of liver metastases. In this study, we attempted to summarize the characteristics of diagnosis and treatment of liver metastases based on our patients and other cases reported in the literatures. Materials and methods: We reviewed the archive files of all patients diagnosed as PC with liver metastases at our center between 2000 and 2022, summarize their clinical presentation, diagnosis, and treatment information. Results: Three patients with liver metastases were included in the study. All patients had pHPT with more or less remission of hypercalcemia after each operation. Liver metastases were mostly detected by CT and MRI examinations. All three cases of liver metastases were surgically resected, one case recurred three years after operation, and radiofrequency ablation (RFA) was performed subsequently. Conclusions: PC is a rare malignant tumor prone to recurrences and metastases, postoperative review should be carried out routinely. Abnormally elevated parathyroid hormone(PTH) and serum calcium can indicate the recurrences or metastases. Enhanced CT and MRI can provide valuable support for the diagnosis of liver metastases, but whether [18F]FDG-PET-CT or [11C] choline-PET-CT can be used as a diagnostic basis needs further studies to improve. Resection of liver metastases or segmental hepatectomy can significantly improve the symptoms of patients. RFA is also a method worth considering in the management of liver metastases.